2015
DOI: 10.1007/s11999-015-4320-z
|View full text |Cite
|
Sign up to set email alerts
|

Does Blast Medium Affect Heterotopic Ossification in a Blast-amputation Model?

Abstract: Background Heterotopic ossification (HO) develops after nearly 2 .3 of traumatic blast amputations in the contemporary battlefield. This phenomenon has potentially devastating consequences for servicemen and women and its pathophysiology warrants further investigation using a previously developed animal blast model. Questions/purposesWe asked, what is the (1) severity (quantity) and (2) type (location) of HO bone formation after a hindlimb blast amputation with two distinct blast media. We hypothesized that a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Tannous et al 52 utilized this method in a rat model, to demonstrate that hindlimb amputation leads to significantly higher rates of HO than forelimb amputation. Utilizing the same procedure, Jaffe et al 53 reported that the type of blast media (sand vs water) has no difference on the development or the severity of HO.…”
Section: Models To Study Trauma-induced Homentioning
confidence: 99%
“…Tannous et al 52 utilized this method in a rat model, to demonstrate that hindlimb amputation leads to significantly higher rates of HO than forelimb amputation. Utilizing the same procedure, Jaffe et al 53 reported that the type of blast media (sand vs water) has no difference on the development or the severity of HO.…”
Section: Models To Study Trauma-induced Homentioning
confidence: 99%
“…The researchers from Pellegrini’s lab established the HO rat model following blast Am procedure, and found that HO demonstrated early fibroproliferative signature. 17,18 In addition, the study from Forsberg and Potter’s lab confirmed that the serum from HO patients could activate mitogen activated protein kinase signaling in adipose stem cells. 19 The authors from Levi and Davis’s Lab found that BMP signaling made great contribution to osteogenic differentiation as well as ectopic bone formation and blocking BMP signaling may be an effective prophylactic strategy for HO following blast-related lower extremity trauma.…”
Section: Discussionmentioning
confidence: 92%
“…The animal study protocol was approved by Animal Care and Use Committee of our institution (Protocol No. 18,032,493). A total of 42 mice (8-10 weeks old, male C57BL/6J mice), purchased from Jackson laboratory, were randomly divided into three groups: Am group (Am of right hindlimb, n = 12), CTX group (CTX injection in the calf muscle of left hindlimb, n = 12) and Am + CTX group (the combination of Am and CTX injection, first Am of right hindlimb, subsequently CTX injection in the calf muscle of left hindlimb, n = 18).…”
Section: The Induction Of Homentioning
confidence: 99%
“…Prior work has developed various rat models in which a shock tube is used to investigate the impact of different magnitudes and duration of the blast pressure in inducing inflammation. 29 Others used a pentaerythritol tetranitrate explosive, submerged beneath a water tank 30 or sand container 31 to induce the fracture. The majority of these models used blast and a separate drop weight to create the fracture.…”
Section: Introductionmentioning
confidence: 99%